Aulus Gellius und die ›Noctes Atticae‹ Die literarische Konstruktion einer Sammlung - Beer, Beate (Millennium-Studien / Millennium Studies, 2020)
Aulus Gellius' Noctes Atticae is a collection of short texts that pursues an aesthetic of variation. Beer's study is an appraisal of the texts and the collection in general. The author analyzes Noctes Atticae based on narratological criteria, develops associative links between the sections, and illuminates the agonal relationship between narrator and implicit reader.